Kierkegaard on offense - Reyes, Jeremiah A (2008)
Kierkegaard presents a very distinct vision of what the christian life ought to be like. Perhaps one word that can sum up this vision and distinguish it from the Christianity he denounced is the word "offense." In this paper we would like to achieve three basic things: (1) To explain and summarize Kierkegaard's concept of offense from his various works. (2) To defend his concept of offense as an inseperable part of Biblical Christianity. (3) To identify its necessary implications in Kierkegaard's existential philosophy.
"June 2008."
Thesis (M.A. Philosophy)--University of the Philippines Diliman.
Keywords: Kierkegaard, Sren Aabye,1813-1855 -- Criticism and interpretation -- History; Existentialism; Christianity -- Philosophy